Matrix metallopeptidases regulate granulosa cell remodeling through the hormone signaling pathway - Kim, Sang Hwan; Yoon, Jong Taek (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: Granulosa cells (GCs) play a very important role in reproductive physiology due to their effect on developmental and functional changes. However, there are differing views regarding the mechanism by which hormones stimulate GCs. Therefore, our study aims to determine whether GCs, in the absence of initial stimulation (17β-estradiol), select specific types of MMPs that reconstitute cells by stimulation of major hormones [follicle-stimulating hormone (FSH) or/ and luteinizing hormone (LH)]. Materials and methods: Early GCs were extracted from immature follicles of the porcine ovary to analyze the MMPs levels. Using early GCs in pigs, the cell development rate was evaluated by adding 17β-estradiol, FSH, LH, or FSH + LH, respectively, to the DMEM containing 10% FBS. Real-time PCR, zymography, enzyme-linked immunosorbent assay, western blot, and immunofluorescence analysis were also performed to determine the MMPs activation in the GCs. Results: Our results confirm that FSH or LH stimulation regulates cell development and intracellular MMPs. In particular, FSH activity kept the MMP-2 and MMP-9 expressions constant in GCs. Conversely, LH activity initially led to rapid increases in the MMP-9 expression, which 96 h later was similar to the MMP-2 expression. Simultaneous utilization of FSH + LH maintained a steady MMP-9 expression and the development of GCs increased. Additionally, when FSH and LH were processed simultaneously, the number of cells increased without changes in cell size, while the cell size changed when LH alone was used. Conclusion: Therefore, the results of this study confirm that even without the initial stimulation of GCs, physiological changes occur according to hormonal changes in the environment, and there is variability in the expression of MMPs. Adv. Vet. Anim. Res., 7(2): 367-373, June 2020